Odpowiedzi

2010-01-06T19:36:59+01:00
2x-11y=73|*3
3x-4y=47|*(-2)

6x-33y=219
-6x+8y=-94
_______________
-25y=125
y=-5

3x-4*(-5)=47
3x+20=47
3x=27
x=9
y=-5
1 5 1
2010-01-06T19:37:07+01:00
2x-11y=73 /*(-3)
3x-4y=47 /*2

-6x+33y=-219
6x-8y=94
---------------
25y=-125 /:25
y=-5

3x=47+4y
3x=47+4(-5)=47-20=27 /:3
x=9

x=9
y=-5
1 5 1
Najlepsza Odpowiedź!
2010-01-06T19:52:24+01:00
2x - 11y = 73
3x - 4y = 47

2x- 11y= 73 /*3
3x- 4y= 47/*(-2)

6x - 33y = 219
-6x + 8y = -94
---------------------------------
-25y = 125 / (-25)
y=-5


--------------------------------
3x- 4y = 47
3x- 4*(-5) = 47
3x - (-20) = 47
3x + 20 = 47
3x=27 / 3
x=9

x = 9
y= -5
y=-5
1 5 1